THE EFFECT OF STUDENTS' LEARNING JOURNAL ON THE CONCEPT OF KINGDOM PLANTAE IN ACEH BESAR - Fatemah Rosma; Vivi Yunisa Harahap (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2022)
This study aims to determine the use of learning journals in motivating students' learning. Data collection was carried out from March to April 2022. The research method was an experiment with a One Group Pretest-posttest Design. The research sample amounted to 30 students. The research instrument was a learning journal to see the reflection of students and a learning motivation questionnaire to see the results of students' learning motivation. Data analysis used the Independent Sample t-test at a significant level of 0.05. The results showed that the use of learning journals with a value of tcount (2,342) ttable (2,000). The highest learning journal aspect is the indicator of material understanding with a value of 3.68. The value of students' learning motivation with a value of tcount (6,254) ttable (2,000). The highest learning motivation aspect is on the relevance indicator with a value of 2.88. It can be concluded that the use of learning journals can motivate students' learning at Dayah Insan Qurani.Keywords: Learning Journal, Learning Motivation.